Origin and mitigation of the beam-induced surface modifications of the LHC beam screens. Issue 1 (1st January 2023) - Petit, V; Chiggiato, P; Himmerlich, M; Marinoni, S; Neupert, H; Taborelli, M; Tavian, L
Abstract: All over Run 2, the LHC beam-induced heat load on the cryogenic system exhibited a wide scattering along the ring. Studies ascribed the heat source to electron cloud build-up, indicating an unexpected high Secondary Electron Yield (SEY) of the beam screen surface in some LHC regions. The inner copper surface of high and low heat load beam screens, extracted during the Long Shutdown 2, was analysed. On the low heat load ones, the surface was covered with the native Cu2 O oxide, while on the high heat load ones CuO dominated at surface, and it exhibited a very low carbon coverage. Such chemical modifications increase the SEY and inhibit a proper conditioning of the affected surfaces. Following this characterisation, the mechanisms for CuO build-up in the LHC beam pipe were investigated on a newly commissioned cryogenic system allowing electron irradiation, surface chemical characterisation by X-ray Photoelectron Spectroscopy and SEY measurements on samples held below 15 K. In parallel, curative solutions against the presence of CuO in the LHC beam screens were explored, which could be implemented in-situ to recover a proper conditioning and lower the beam-induced heat load.